Results of surgical management of renal cell carcinoma metastatic to the pancreas - Kusnierz, Katarzyna; Mrowiec, Slawomir; Lampe, Pawel (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Metastases from renal cell carcinoma represent between 0.25 and 3.00% of all resected pancreatic tumours. The aim of this study was to review 13 patients with renal cell carcinoma metastatic to the pancreas. Material and methods: Clinical data, time from initial presentation, operative outcome, long-term survival, tumour size, presence of lymphatic invasion, and surgical margin status were evaluated. Results: The median age of the patients was 62 years (mean 60.9). The median time for appearance of metastatic disease following resection of the primary tumour was 9 years (mean 8.38). Pancreatic metastases were located in the head of the pancreas in four patients, in the body in three, in the tail in two patients, and four patients had multiple pancreatic localisations. Four (30.7%) pancreatoduodenectomies, 5 (38.5%) distal resections, 2 (15.3%) total pancreatectomies, 1 (7.6%) enucleation, and 1 (7.6%) Roux duodenojejunostomy were performed. Two patients (15.3%) had postoperative complications. Operative mortality was 0%. Surgical margins were microscopically positive in 1 (8.3%) patient, and lymph nodes were positive in 2 (16.6%) patients. In our group of 7 deceased patients the mean survival was 19 months (median 16 months). Conclusions : Renal cell carcinoma metastatic to the pancreas can occur several years after nephrectomy. In our series a large number of patients with occurrence of symptoms, advancement of tumours, metastases to lymph node, and positive margin were connected with short survival period. Early detection of primary tumour, long and thorough patient care, and radical resections give patients a chance for a prolonged life.